Antibiotic susceptibility of Aggregatibacter actinomycetemcomitans JP2 in a biofilm - Orit Oettinger-Barak; Stuart G. Dashper; Deanne V. Catmull; Geoffrey G. Adams; Michael N. Sela; Eli E. Machtei; Eric C. Reynolds (Journal of Oral Microbiology, 2013)
Background: Localized aggressive periodontitis (LAgP) is an inflammatory disease associated with specific bacteria, particularly Aggregatibacter actinomycetemcomitans, which can result in early tooth loss. The bacteria grow as a biofilm known as subgingival plaque. Treatment includes mechanical debridement of the biofilm, often associated with empirical antibiotic treatment. Objective: The aims of this study were to test in vitro the sensitivity of A. actinomycetemcomitans JP2 during planktonic and biofilm growth to doxycycline and to the combination of metronidazole and amoxicillin, which are two antibiotic protocols commonly used in clinical practice. Design: Two in vitro biofilm models were used to test the effects of the antibiotics: a static 96-well plate assay was used to investigate the effect of these antibiotics on biofilm formation whilst a flow chamber model was used to examine the effect on established biofilms. Results: Of the antibiotics tested in this model system, doxycycline was most efficacious with a minimal inhibitory concentration (MIC) against planktonic cells of 0.21 mg/L and minimal biofilm inhibitory concentration (MBIC) of 2.10 mg/L. The most commonly prescribed antibiotic regimen, amoxicillin + metronidazole, was much less effective against both planktonic and biofilm cells with an MIC and MBIC of 12.0 mg/L and 20.2 mg/L, respectively. A single treatment of the clinically achievable concentration of 10 mg/L doxycycline to sparse A. actinomycetemcomitans biofilms in the flow chamber model resulted in significant decreases in biofilm thickness, biovolume, and cell viability. Dense A. actinomycetemcomitans biofilms were significantly more resistant to doxycycline treatment. Low concentrations of antibiotics enhanced biofilm formation. Conclusion: A. actinomycetemcomitans JP2 homotypic biofilms were more susceptible in vitro to doxycycline than amoxicillin + metronidazole.